Polymeric Caffeic Acid Acts as a Nasal Vaccine Formulation against Streptococcus pneumoniae Infections in Mice - Rui Tada; Hidehiko Suzuki; Miki Ogasawara; Daisuke Yamanaka; Yoshiyuki Adachi; Jun Kunisawa; Yoichi Negishi (MDPI AG, 2021)
Infectious diseases are the second leading cause of death worldwide, highlighting the importance of the development of a novel and improved strategy for fighting pathogenic microbes. Streptococcus pneumoniae is a highly pathogenic bacteria that causes pneumonia with high mortality rates, especially in children and elderly individuals. To solve these issues, a mucosal vaccine system would be the best solution for the prevention and treatment of these diseases. We have recently reported that enzymatically polymerized caffeic acid (pCA) acts as a mucosal adjuvant when co-administered with antigenic proteins via the nasal route. Moreover, the sources of caffeic acid and horseradish peroxidase are ingredients found commonly in coffee beans and horseradish, respectively. In this study, we aimed to develop a pneumococcal nasal vaccine comprising pneumococcal surface protein A (PspA) and pCA as the mucosal adjuvant. Intranasal immunization with PspA and pCA induced the production of PspA-specific antibody responses in the mucosal and systemic compartments. Furthermore, the protective effects were tested in a murine model of S. pneumoniae infection. Intranasal vaccination conferred antigen-dependent protective immunity against a lethal infection of S. pneumoniae. In conclusion, pCA is useful as a serotype-independent universal nasal pneumococcal vaccine formulation.